2021
DOI: 10.32598/rj.21.4.555.2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Public Participation in Health Legislation in Iran: A Qualitative Study

Abstract: Objective: This study aims to identify the challenges for public participation in health legislation in Iran. Materials & Methods: This is an exploratory and qualitative study. The study data were collected by using semi-structured interviews. The participants were experts in the field of health law with at least ten years of work experience. They had both experience and enough knowledge about the country’s health system. All interviews were transcribed verbatim after recording and then analyzed using them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, governments can use the capacity of NGOs to strengthen their country's health system, which requires long-term planning, adequate funding, and a culture of participation ( 28 ). Policy barriers need to be removed by creating a necessary legal framework, developing trust and societal acceptance of NGOs' activities and involvement, and training and empowering NGOs in health ( 3 , 31 , 32 , 69 ). Also, the latest research on the role of NGOs in Iran's health system found that NGOs play different roles in Iran's health system, but they are ignored and appropriate strategies need to be applied ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, governments can use the capacity of NGOs to strengthen their country's health system, which requires long-term planning, adequate funding, and a culture of participation ( 28 ). Policy barriers need to be removed by creating a necessary legal framework, developing trust and societal acceptance of NGOs' activities and involvement, and training and empowering NGOs in health ( 3 , 31 , 32 , 69 ). Also, the latest research on the role of NGOs in Iran's health system found that NGOs play different roles in Iran's health system, but they are ignored and appropriate strategies need to be applied ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tailand [8,11,20] Iran [8,[21][22][23][24][25][26] Chile [27][28][29][30][31][32][33][34][35][36][37][38][39] France [8,[40][41][42][43][44][45] Tunisia [8,[46][47][48][49][50][51][52][53][54] Origin of demand for participation Despite the fact that the model designed for Tunisia is based on the successful model of Tailand, the "Societal Dialogue for Health System Reform" program is still far from realization of its goals for reasons including lack of political and managerial stability, lack of trust, and tension between citizens and health professionals [54].…”
Section: Teme Subthemementioning
confidence: 99%
“…Tailand [8,11,20] Iran [8,[21][22][23][24][25][26] Chile [27][28][29][30][31][32][33][34][35][36][37][38][39] France [8,[40][41][42][43][44][45] Tunisia [8, 46-…”
Section: Temementioning
confidence: 99%